Chlorophyll fluorescence imaging analysis of the responses of Antarctic bottom-ice algae to light and salinity during melting - Ryan, KG; Tay, ML; Martin, AR; Andrew McMinn; Davy, SK (2011)
Bottom-ice algae within Antarctic sea ice were examined using chlorophyll fluorescence imaging. The detailed structure of the bottom-ice algal community growing in the platelet and congelation layers of solid pieces of sea ice was evident for the first time in chlorophyll imaging mode. Strands of fluorescence representing algal cells were clearly visible growing upward into brine channels in a fine network. Images of effective quantum yield (ÔPSII) revealed that theÔPSII of algae embedded in the sea ice was approximately 0.5. Furthermore,ÔPSII decreased slightly with distance from the ice–water interface. The response of Antarctic sea ice algae to changes in irradiance and salinity, and the effects of slowly warming and melting the ice block sample were examined using this system. The ÔPSII of bottom-ice algae decreased as irradiance increased and salinities decreased. Bottom-ice algae appear to be most vulnerable to changes in their environment during the melting process of the ice, and this suggests that algae from this region of the ice may not be able to cope with the stress of melting during summer. Chlorophyll fluorescence imaging provides unprecedented imagery of chlorophyll distribution in sea ice and allows measurement of the responses of sea ice algae to environmental stresses with minimal disruption to their physical habitat. The results obtained with this method are comparable to those obtained with algae that have been melted into liquid culture and this indicates that previous melting protocols reveal meaningful data. In this chlorophyll imaging study, rapid light curves did not saturate and this may prevent further use of this configuration.